Translation Today Vol. VIII No. II - (:unkn) unknown (My University, 2014)
This issue also focuses on the impact of technology and globalization on Indian languages. Subtitling and dubbing, as the newly emerging areas in the field of Translation, also occupies space in this issue.
Keywords: English